THE CORRELATION BETWEEN PARENT’S ECONOMIC LEVEL AND BOREDOM IN LEARNING WITH STRESS AMONG STUDENTS DURING COVID-19 PANDEMIC - Dwi Faqihatus Syarifah Has; Eka Srirahayu Ariestinigsih (Indonesian Journal of Community Health Nursing, 2022)
IntroductionThe COVID-19 pandemic is a global crisis with far-reaching consequences. Increasing numbersof deaths worldwide, communities and economies face extreme pressure both from the directimpact of the virus and the indirect effects of measures to prevent transmission. In many countries,food systems are increasingly vulnerable to disruption, Health systems are overburdened,education systems are substantially altered, and social protection systems face a sharp increase indemand as a result of a sudden economic downturn and rapidly rising unemployment. As theclinical impact of COVID-19 is better understood, many families experience, or will soonexperience, major difficulties due to disruption of essential services and loss of income.Method : Analytical obrservasional research with cross sectional research design with a samplenumber of 186 students, sampling techniques using simple random sampling. The instrument usedto conduct the study is a questionnaire and a stress measuring tool using the Perceved Stress Scale(PSS-10) which will be given to respondents through the google from link, where respondentsanswer questions in accordance with the instructions that have been set in each questionnaire.Result : Chi-Square test results with an error rate of 5% (0.05) obtained Sig (0.493) > α (0.05),Then H1 rejected H0 accepted means there is no relationship between family economy and studentstress levels in pandemic times and Chi-Square test results with error rate of 5% (0.05) obtainedsig value (0.000) < α (0.05), then H1 received H0 is noted to mean there is a relationship betweensaturation of learning and student stress levels in pandemic times. The results of the multivariatetest, obtained a strong association of saturation levels with student stress events were 2,259. So itcan be concluded if students experience saturation it will cause a 2-fold risk to suffer from stress.Conclusion: There is no relationship between family economics and student stress levels inpandemic times, but there is a relationship between saturation of learning and student stress levelsin pandemic times.